2012
DOI: 10.1097/jgp.0b013e318227f4da
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib or Naproxen Treatment Does Not Benefit Depressive Symptoms in Persons Age 70 and Older: Findings From a Randomized Controlled Trial

Abstract: Background Several lines of evidence suggest that inflammatory mechanisms may be involved in the severity and progression of depression. One pathway implicated is the production of prostaglandins via the enzyme cyclooxygenase (COX). Although late life depression in particular has been associated with inflammation, we know of no published studies using COX inhibitors, such as nonsteroidal anti-inflammatory drugs (NSAIDs), in the treatment of depressive syndromes in this population. Objective To evaluate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 46 publications
0
59
0
3
Order By: Relevance
“…These studies suggest an adjuvant role for NSAIDs in TRD treatment. In contrast, a large scale randomized controlled trial designed to evaluate NSAID treatment (celecoxib & naproxen) in approximately 2,500 elderly adults with late-life depression found no significant effect in reducing modified Geriatric Depression Scale (GDS) scores compared to placebo (Fields et al, 2012), suggesting that antiinflammatory monotherapy may be insufficient to produce significant antidepressant effects.…”
Section: Effects Of Anti-inflammatory Medications On Depressionmentioning
confidence: 94%
“…These studies suggest an adjuvant role for NSAIDs in TRD treatment. In contrast, a large scale randomized controlled trial designed to evaluate NSAID treatment (celecoxib & naproxen) in approximately 2,500 elderly adults with late-life depression found no significant effect in reducing modified Geriatric Depression Scale (GDS) scores compared to placebo (Fields et al, 2012), suggesting that antiinflammatory monotherapy may be insufficient to produce significant antidepressant effects.…”
Section: Effects Of Anti-inflammatory Medications On Depressionmentioning
confidence: 94%
“…The number of studies of COX-2 inhibitors in depression is relatively small (n = 5, excluding acetylsalicylic acid), despite the fact that no less than 3 meta-analyses of these studies have appeared in the literature (threatening to outnumber the number of primary studies themselves; Faridhosseini et al, 2014;Kohler et al, 2014;Na et al, 2014). The largest of these studies was a randomized, placebo-controlled preventative trial that included over 4000 patients and showed no advantage of the COX-2 inhibitor celecoxib over placebo in preventing the development of depression in an elderly cohort of subjects (Fields et al, 2012). Of the 4 remaining trials, all were small (~n = 20 per group) and all used celecoxib versus placebo as an add-on to a conventional antidepressant in patients with major depression.…”
Section: Reviewmentioning
confidence: 99%
“…Another RCT tested celecoxib as an add-on to fluoxetine, showing the superiority of the association [68]. Celecoxib has also shown promising results as an adjuvant in the treatment of bipolar depression and schizophrenia [69,70,71], but has negative results in improving depressive symptomatology in cognitively normal volunteers aged 70 years and older with a family history of Alzheimer-like dementia [72]. …”
Section: The Future Of Research On Inflammation In Mddmentioning
confidence: 99%